Digital Democracy in Popular Culture: Nurhadi-Aldo as Meme and Political Critics - Saniscara, Pramesti (Universitas Ciputra, 2019)
Digital Democracy in Popular Culture: Meme and Political Critics. Meme has become a popular subculture that cannot be separated from the internet sphere. Meme have become an agent of free speech that allows a discourse to be communicated, changed, dispersed without the need of conventional conversation. The upcoming Presidential Election 2019 in Indonesia has become one of the discourses that often, using memes as its agent. Memes, while being a medium of expressed humor and satire, also become a media critic of Indonesian democracy practices. This research is a descriptive qualitative research with data collection method through observation and literature studies. This journal sees the meme of Nurhadi-Aldo as a discourse of political criticism wrapped in comedy and satire in response to the 2019 Presidential Election using structuralism approach from Anthony Giddens.